Poetry and the Extremities of Language: From Concretism to Paul Celan - James K. Lyon (Studies in 20th & 21st Century Literature, 1983)
Despite his disdain for most contemporary German language poets, Paul Celan in his own verse shares and reflects in several ways the attitudes toward language and the possibilities of poetic speech found in the practitioners of so-called "concrete poetry." Skeptical of language that had fallen victim to the "verbicide" of modern usage, each set out to re-create or revitalize language by using it in an anti-metaphorical sense where words, rather than functioning as bearers of meaning, are often employed as unconventional, in some cases anti-referential sign systems that have meaning only in relationship to themselves, but which simultaneously attempt to create (or discover) a pristine language. Beyond the affinity of theoretical statements made by Celan and the concrete poets, their practices of punning, word play, word deformation, reduction of words to component letters and sounds, the emphasis on the optical appearance of words and poems, and attempts to probe the essence of words by devices such as punctuation, citation, and negation all suggest that, differences notwithstanding, they shared and sought to overcome a commonly-perceived crisis of the possibilities of poetic language by a number of common means.
Keywords: German language poets; Paul Celan; verbicide; modern; poem; poetry; poetics; anti-metaphorical; anti-referential; sign; punning; word play; word deformation; component letters; sounds; punctuation; citation; negation; devices; poetic language